Royal Victoria Institute, Trinidad - (:unkn) unknown (Davidson and Todd Ltd., Trinidad, 2010)
The postcard shows the Victoria Institute which built to commemorate the Golden Jubilee of Queen Victoria’s reign. Fire gutted the building 19th May, 1920 and it was rebuilt by June 1923 but renamed the National Museum and Art Gallery in 1965. The original building was designed by Daniel Meinerts Hahn, Chief Draughtsman at the Department of Public Works, Trinidad. In the foreground is Memorial Park. The postcard is addressed to Mr. Geo Kouchakji of Brooklyn, United States of America and the card is postmarked April 1919.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Historical buildings--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; National museums--Trinidad and Tobago; 1919; Parks--Trinidad and Tobago; Trees--Trinidad and Tobago; Fences--Trinidad and Tobago; Shrubs--Trinidad and Tobago; Architecture--Trinidad and Tobago; Museums--Trinidad and Tobago; Windows--Trinidad and Tobago; Queens—-Great Britain; Memorial Park (Port of Spain); Daniel Meinerts Hahn